BEL1-like Homeodomain Protein BLH6a Is a Negative Regulator of CAld5H2 in Sinapyl Alcohol Monolignol Biosynthesis in Poplar - Wang, Qiao; Dai, Xinren; Pang, Hongying; Cheng, Yanxia; Huang, Xiong; Li, Hui; Yan, Xiaojing; Lu, Fachuang; Wei, Hairong; Sederoff, Ronald R.; Li, Quanzi (Frontiers in Plant Science, 2021)
Lignin is one of the major components of xylem cell walls in tree stems. The lignin in the wood of most flowering plants (dicotyledonous angiosperms) is typically polymerized from three monolignol precursors, coniferyl alcohol, sinapyl alcohol, and p-coumaroyl alcohol, resulting in guaiacyl (G), syringyl (S), and hydroxyphenyl (H) subunits, respectively. In this study, we focus on the transcriptional regulation of a coniferaldehyde 5-hydroxylase (CAld5H2) gene, which encodes a key enzyme for sinapyl alcohol biosynthesis. We carried out a yeast one-hybrid (Y1H) screen to identify candidate upstream transcription factors (TFs) regulating CAld5H2. We obtained 12 upstream TFs as potential regulators of CAld5H2. One of these TF genes, BLH6a, encodes a BEL1-like homeodomain (BLH) protein and negatively regulated the CAld5H2 promoter activity. The direct regulation of CAld5H2 promoter by BLH6a was supported by chromatin immunoprecipitation–quantitative polymerase chain reaction (ChIP–qPCR) and dominant repression of BLH6a in transgenic plants. Luciferase complementation imaging analyses showed extensive protein–protein interactions among these 12 TFs. We propose that BLH6a is a negative regulator of CAld5H2, which acts through combinatorial regulation of multiple TFs for sinapyl alcohol (S monolignol) biosynthesis in poplar.